EFFECTS OF PREGNANCY ON THE PROGRESSION OF METABOLIC SYNDROME COMPONENTS - I. O. Makarov; E. M. Shilov; M. S. Novikova; E. I. Borovkova (IRBIS LLC, 2016)
The article presents the results of a prospective cohort study that investigated changes in principal components of the metabolic syndrome (MS) in women in the course of a pregnancy and an assessment of these components in the postnatal period. The presented study has demonstrated that the metabolic syndrome deteriorates the course of pregnancy. This condition is an indication for complex evaluation by physicians of various specialities, strict control of the metabolic profile, and early administration of renal protectors